2016
DOI: 10.1016/j.athoracsur.2015.05.113
|View full text |Cite
|
Sign up to set email alerts
|

Early Surgical Outcomes of En Bloc Resection Requiring Vertebrectomy for Malignancy Invading the Thoracic Spine

Abstract: En bloc vertebrectomy for malignant disease is feasible. Our 1 stage and 2 team approach allows completion of the operation within a standard day, but is associated with long operative time. Complication rates may improve with decreased operative times. Review of available data warrants future prospective studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 15 publications
2
18
0
Order By: Relevance
“…Mean blood loss after surgical decompression of spinal tumors ranges from 500 to 2300 mL and these procedures are associated with high transfusion rates. 1,20,41-43 Minimizing blood loss and perioperative transfusions not only reduces health care costs 14,15,44,45 but may also play a role in reducing perioperative mortality. 46-50 Perioperative transfusion of allogeneic blood has also been associated with higher infection rates following various orthopedic procedures, 48,51-55 and in this study, 48.6% of patients with perioperative sepsis had received a perioperative blood transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Mean blood loss after surgical decompression of spinal tumors ranges from 500 to 2300 mL and these procedures are associated with high transfusion rates. 1,20,41-43 Minimizing blood loss and perioperative transfusions not only reduces health care costs 14,15,44,45 but may also play a role in reducing perioperative mortality. 46-50 Perioperative transfusion of allogeneic blood has also been associated with higher infection rates following various orthopedic procedures, 48,51-55 and in this study, 48.6% of patients with perioperative sepsis had received a perioperative blood transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Mody et al reported on a large case series of extended resection for tumor invading the thoracic spine and requiring vertebrectomy. Sarcoma was present in 9 of the 32 cases with 82% achieving an R0 resection [55]. …”
Section: Complex Managementmentioning
confidence: 99%
“…Later, Smitherman et al applied frameless stereotactic navigation to complete a multi-level sagittal vertebral osteotomy for a giant cell tumor, claiming that real-time three-dimensional imaging made the procedure possible by avoiding adjacent critical vascular structures [ 15 ]. Furthermore, Mody et al contributed to the sequence of en bloc resection by splitting up the procedure into two stages, allowing for completion in a standard day [ 16 ]. Kobayashi et al, who published their case report just a few days after we performed our case, applied the use of an O-Arm stereotactic navigation system to partial vertebrectomy for lung cancer adjacent to the thoracic spine, stating the O-Arm permitted accurate confirmation of the surgical margins of the osteotomy via a posterior approach [ 17 ].…”
Section: Discussionmentioning
confidence: 99%